A Socio - Environmental Investigation of Inaccessibility of Drinking Water in India - Ranjan, Avinash; Wadini, Priya; Meena, Mukesh Kumar (National Geographical Journal of India, 2022)
Access to water is shaped by various factors such as physical characteristics of the water cycle, i.e., the availability, geographical location, geological structure, techno-managerial setup, water infrastructure, and socio-political organization. Despite the efforts at global, regional and local levels; still, millions of people do not have the accessibility of drinking water to their households. Similarly, India is facing the worst water crisis of its history where more than 20 mega cities are running out of the water or are on the verge of it. The primary goal of this paper was to identify all the factors and incorporate them into a single study that are responsible for the crisis of drinking water in India. To achieve our goal, we have reviewed the various literature available online and ofine.Furthermore, reports from the Central Groundwater Board, National Sample Survey Ofce, Food and Agriculture Organization, World Health Organization, United Nations Children Emergency Fund etc. have been reviewed and analyzed. Microsoft Excel and ArcGIS 10.4.1 have been used to analyze and to represent the data obtained. This study observes that the socio-political factors are playing a signicant role in the accessibility/inaccessibility of water in India. Moreover, factors like change in cropping pattern, inadequate infrastructure, the problem oeakages in cities, inefciency in surface water utilization, contamination of groundwater by heavy metals, discrepancies in scientic solution, etc. are also keeping the people away from one of the essential resources for the substance for human life